Literature Review: Factors Risks that Influence the Incidence of Stunting - Ariani, Dini; Septiani , Hani; Srinayanti, Yanti; Solihah, Rosidah (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2024)
Introduction: Stunting is associated with impaired growth and development in children. In the short term, it can cause problems such as: an upward trend in the morbidity and mortality rate of children, decreased intelligence, motor disorders, increased spending on health, and increased costs for health care and disease treatment. Meanwhile, in the long term, they include decreased height in adult children, decreased reproductive health, low activity at school, less potential learning capacity, and low work capacity and productivity. Objective: The purpose of this research is to review the literature, articles, and results documents of research on factors that influence the incidence of stunting. Method: The method used in writing this article is a review of the results of a study the research on factors that influence the incidence of stunting. The type of data in this literature review study were obtained by tracing scientific research articles from 2022-2024 using a data base such as Pubmed, google schoolar. Result: Many kinds of the risks to related the stunting. There are associated with stunting, namely residence, age of mother, mother’s education, mother’s occupation, economic status, child’s age, gender, EBFI, having no access to safe drinking water, not proper sanitation, and poor maternal hygiene practices. The other the risks to related the stunting were marital status, before pregnancy, during pregnancy, postnatal, infectious disease factors and socia-demographic factors. Conclusion: This review concluced that average risks to related the stunting were maternal age, maternal education, recidence, employement, child’s age, gender, economic status.